Cardiovascular surgery in cancer patients — a new challenge for hybrid surgery - T. E. Imaev; A. E. Komlev; R. S. Akchurin (Кардиоваскулярная терапия и профилактика)
Aim. To analyze own experience of hybrid and endovascular treatment of patients with combined cardiac surgery and oncological pathology. Material and methods. A retrospective study included 185 patients (52-92 years) with cancer pathology — 15,7% of the total number of patients who were operated on at the Department of Cardiovascular Surgery in 2010-2018 using transcatheter methods. In 135 high-risk patients, transcatheter implantation of the aortic valve was performed (35% men, group 1), endovascular and hybrid operations for aortic aneurysm were performed in 50 patients (96% men, group 2).Results. Among the operated cardiac surgery patients, prostate cancer was in top of concomitant oncopathologies in men (47%), in women — breast cancer (39%). Malignant tumors of the gastrointestinal tract (19%) and lymphogranulomatosis of intrathoracic localization (11% of men and 2% of women) were also common in patients of group 1. In group 2, colon and lung cancer was in 16% of patients, kidney cancer in14%, bladder cancer in 8% of patients. Statistically significant differences were found in the frequency of the following neoplasms: kidney cancer — 4,4% and 14% (p<0,02); colon cancer — 10,3% and 16% (p<0,02) in group 1 and 2, respectively. After surgery, 42% of patients from group 1 and 52% of group 2 were referred for further oncological treatment.Conclusion. Among patients of older age groups with cardiovascular pathology, the prevalence of concomitant cancer is high. The possibilities of hybrid cardiovascular surgery can be successfully used to provide surgical care to patients with malignant neoplasms, even if conventional surgical treatment is not possible or characterized by extremely high risk.